Hippocampal BAIAP2 prevents chronic mild stress-induced depression-like behaviors in mice - Fu, Yaling; Guo, Xiangfei; Yang, Rui; Feng, Hao; Yin, Xueyong; Wang, Shuang; Song, Li; Wang, Xi; Zhao, Penghui; Wang, Sheng; Shi, Yun; Shi, Haishui (Frontiers in Psychiatry, 2023)
Background The pathogenesis of depression is closely related to changes in hippocampal synaptic plasticity; however, the underlying mechanism is still unclear. Brain-specific angiogenesis inhibitor 1-associated protein 2 (BAIAP2), a postsynaptic scaffold protein in excitatory synapses important for synaptic plasticity, is highly expressed in the hippocampus and has been implicated in several psychiatric disorders. However, the role of BAIAP2 in depression remains poorly understood. Methods In the present study, a mouse model of depression was established via exposure to chronic mild stress (CMS). An adeno-associated virus (AAV) vector expressing BAIAP2 was injected into the hippocampal brain region of mice and a BAIAP2 overexpression plasmid was transfected into HT22 cells to upregulate BAIAP2 expression. Depression- and anxiety-like behaviors and dendritic spine density were examined in mice using behavioral tests and Golgi staining, respectively. In vitro, hippocampal HT22 cells were treated with corticosterone (CORT) to simulate the stress state, and the effect of BAIAP2 on CORT-induced cell injury was explored. Reverse transcription-quantitative PCR and western blotting were employed to determine the expression levels of BAIAP2 and those of the synaptic plasticity-related proteins glutamate receptor ionotropic, AMPA 1 (GluA1), and synapsin 1 (SYN1). Results Mice exposed to CMS exhibited depression- and anxiety-like behaviors accompanied by decreased levels of BAIAP2 in the hippocampus. In vitro, the overexpression of BAIAP2 increased the survival rate of CORT-treated HT22 cells and upregulated the expression of GluA1 and SYN1. Consistent with the in vitro data, the AAV-mediated overexpression of BAIAP2 in the hippocampus of mice significantly inhibited CMS-induced depression-like behavior, concomitant with increases in dendritic spine density and the expression of GluA1 and SYN1 in hippocampal regions. Conclusion Our findings indicate that hippocampal BAIAP2 can prevent stress-induced depression-like behavior and may be a promising target for the treatment of depression or other stress-related diseases.